2014
DOI: 10.7224/1537-2073.2013-003
|View full text |Cite
|
Sign up to set email alerts
|

The TRUST (EvaluaTion of Bladder Function in Relapsing-Remitting MUltiple Sclerosis Patients Treated with Natalizumab) Observational Study

Abstract: Background: Bladder dysfunction is a common symptom of multiple sclerosis (MS). This study was designed to evaluate effects of natalizumab on bladder function in patients with relapsing-remitting MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Early fingolimod vs later fingolimod RCT (TRANSFORMS): 1 year of treatment with fingolimod or IM IFN-β1a Lower relapse rate (Khatri et al, 2011) Fewer new lesions (Khatri et al, 2011) Fewer people with active lesions (Khatri et al, 2011) No effect on disability progression (Khatri et al, 2011) Longer time to next relapse a (Meng et al, 2014) Extension: 1 year of treatment with fingolimod (N¼ 1027; continuous fingolimod: 0.5 mg [n ¼356], 1.25 mg (n ¼330); switch from IM IFN-β1a to fingolimod: 0. Natalizumab vs baseline (before starting treatment with natalizumab) (Khatri et al, 2014) 6 months of treatment with natalizumab in people with MS and disabling bladder dysfunction (N¼ 30) Improvements in incontinence-related quality of life after 6 months compared with baseline All results shown were statistically significant. DMT, disease-modifying therapy; EDSS, Kurtzke Expanded Disability Status Scale; GA, glatiramer acetate; IFN-β, interferon beta; IM, intramuscular; MRI, magnetic resonance imaging; RCT, randomized controlled trial; RWE, real-world evidence; TOP, Tysabri (natalizumab) Observational Program; TRANSFORMS, Efficacy and safety of fingolimod in patients with relapsing-remitting multiple sclerosis with optional extension phase; TRUST, EvaluaTion of Bladder Function in Relapsing-Remitting Multiple Sclerosis Patients Treated with Natalizumab; TYNERGY, Effects of Tysabri (natalizumab) over 12 months on MS-related fatigue in participants with RRMS.…”
Section: Appendix a Recommendationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Early fingolimod vs later fingolimod RCT (TRANSFORMS): 1 year of treatment with fingolimod or IM IFN-β1a Lower relapse rate (Khatri et al, 2011) Fewer new lesions (Khatri et al, 2011) Fewer people with active lesions (Khatri et al, 2011) No effect on disability progression (Khatri et al, 2011) Longer time to next relapse a (Meng et al, 2014) Extension: 1 year of treatment with fingolimod (N¼ 1027; continuous fingolimod: 0.5 mg [n ¼356], 1.25 mg (n ¼330); switch from IM IFN-β1a to fingolimod: 0. Natalizumab vs baseline (before starting treatment with natalizumab) (Khatri et al, 2014) 6 months of treatment with natalizumab in people with MS and disabling bladder dysfunction (N¼ 30) Improvements in incontinence-related quality of life after 6 months compared with baseline All results shown were statistically significant. DMT, disease-modifying therapy; EDSS, Kurtzke Expanded Disability Status Scale; GA, glatiramer acetate; IFN-β, interferon beta; IM, intramuscular; MRI, magnetic resonance imaging; RCT, randomized controlled trial; RWE, real-world evidence; TOP, Tysabri (natalizumab) Observational Program; TRANSFORMS, Efficacy and safety of fingolimod in patients with relapsing-remitting multiple sclerosis with optional extension phase; TRUST, EvaluaTion of Bladder Function in Relapsing-Remitting Multiple Sclerosis Patients Treated with Natalizumab; TYNERGY, Effects of Tysabri (natalizumab) over 12 months on MS-related fatigue in participants with RRMS.…”
Section: Appendix a Recommendationsmentioning
confidence: 95%
“…Several studies have shown that people with MS who switch from an established DMT to a newer DMT (with an evidence base supporting superior efficacy to that of an established DMT) are more likely to be free from relapses (Prosperini et al, 2012;Bergvall et al, 2014;He et al, 2015;Spelman et al, 2015), disability progression (Prosperini et al, 2012;He et al, 2015;Spelman et al, 2015) and new MRI activity (Prosperini et al, 2012) and can even experience improvements in their disability status (He et al, 2015) compared with switching to another established DMT. A number of other studies have demonstrated that improvements in disability (Kallweit et al, 2012;Svenningsson et al, 2013;Butzkueven et al, 2014a;Kalincik et al, 2015a), quality of life measures (Khatri et al, 2014), fatigue (Svenningsson et al, 2013) and cognition (Svenningsson et al, 2013) are also possible when people with MS receive a newer DMT (with an evidence base supporting superior efficacy to that of an established DMT; Table D.1) (Khatri et al, 2011;Kallweit et al, 2012;Prosperini et al, 2012;Svenningsson et al, 2013;Bergvall et al, 2014;Butzkueven et al, 2014;Khatri et al, 2014;Meng et al, 2014;He et al, 2015;Kalincik et al, 2015a;Spelman et al, 2015). As adequate control of disease activity will not always be achieved in all people with MS taking any one DMT, regular monitoring should be the cornerstone of any treatment strategy (Section 8).…”
Section: Choice Of Therapy Should Be An Evidence-based Decisionmentioning
confidence: 99%
“…Several studies have shown that people with MS who switch from an established DMT to a newer DMT (with an evidence base supporting superior efficacy to that of an established DMT) are more likely to be free from relapses Bergvall et al, 2014;He et al, 2015;, disability progression He et al, 2015; and new MRI activity and can even experience improvements in their disability status compared with switching to another established DMT. A number of other studies have demonstrated that improvements in disability Svenningsson et al, 2013;Butzkueven et al, 2014a;Kalincik et al, 2015a), quality of life measures , fatigue and cognition are also possible when people with MS receive a newer DMT (with an evidence base supporting superior efficacy to that of an established DMT; Kallweit et al, 2012;Prosperini et al, 2012;Svenningsson et al, 2013;Baldi et al, 2014;Bergvall et al, 2014;Butzkueven et al, 2014a;Khatri et al, 2014;Meng et al, 2014;He et al, 2015;Kalincik et al, 2015a;Spelman et al, 2015)). As adequate control of disease activity will not always be achieved in all people with MS taking any one DMT, regular monitoring should be the cornerstone of any treatment strategy (Section 4).…”
Section: Choice Of Therapy Should Be An Evidence-based Decisionmentioning
confidence: 99%
“…Finalmente se incluyeron un total de 18 estudios, de los cuales cuatro (22,2%) eran modelizaciones [15][16][17][18], seis estudios evaluaban la calidad de vida en condiciones de práctica clínica habitual tras la administración de natalizumab [19][20][21][22][23][24], tres eran ensayos que evaluaban diferentes medidas de salud reportadas por pacientes (patient reported outcomes [PRO]) [25][26][27] y un estudio evaluaba el efecto de natalizumab sobre la productividad laboral en Suecia [28]. De los restantes dos eran análisis conjuntos [29,30] de los estudios AFFIRM y SENTINEL, estudios clínicos de natalizumab, focalizándose concretamente en evaluar la CVRS, y en tres se aportaban post-hoc análisis del ensayo AFFIRM que relacionaban la capacidad visual [31] y la velocidad de desplazamiento [23,32] con la calidad de vida.…”
Section: Estudios Incluidosunclassified
“…En referencia a los ensayos de medidas de salud percibidas por los pacientes (Tabla 4), el ensayo TRUST [27] evaluó el efecto de natalizumab, demostrando mejorías en la CVRS asociada a incontinencia urinaria determinada con cuestionarios específicos (Urogenital Distress Inventory ; Incontinence Impact Questionnaire [IIQ-7]). A las 24 semanas de tratamiento un 85,7% de los pacientes reportó mejoras en las puntuaciones del UDI-6 respecto al valor basal (p < 0,001) y un 78,6% en los valores de IIQ-7.…”
Section: Estudios De Calidad De Vida Relacionada Con La Salud En La Punclassified